AUSTRALIAN ACCENTS AND DIALECTS IN THE CONTEMPORARY ENGLISH - Amir Abushaev (International Journal of Innovations in Engineering Research and Technology, 2023)
The mainstream Australian accent is a distinct accent produced by native English speakers in Australia. It’s a tough accent to replicate, even for actors in Hollywood.Some speakers may wish to incorporate some local, Australian pronunciation features into their speech patterns. If so, we can assist you by providing you with information on what you might like to add in and how to do it! Other speakers may want to sound more intelligible but neutral, we can also assist you. Australian pronunciation is one of the many speech pronunciation codes we can follow if you wish to work on your pronunciation. Read more about what features you can work on with us to incorporate some rules of Australian English into your pronunciation.